STRATEGI BRANDING PORTAL ONLINE WWW.TRIPRIAU.COM DALAM MEMBANGUN BRAND AWARENESS SEBAGAI PORTAL ONLINE PARIWISATA PROVINSI RIAU - Yuri Rahmadhani; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Online portal www.tripriau.com online portal is one of the online portal in Riau Province that has its own uniqueness. These portals contain local content and the potential of tourism in the province of Riau. Since its establishment, www.tripriau.com do branding strategy in order to build brand awareness or trust the reader to be known as a tourism-themed online portal. As the selection of brand name Trip Riau, Riau Guide My tagline, as well as the implementation of travel instagram photo contest. It aims to reinforce to the public if the company is a media focus on discussing about tourism in the province of Riau. However, along with development, other emerging online portal that also focuses the tourism content alone. This study aims to determine the branding strategy undertaken www.tripriau.com to build brand awareness as an online portal of tourism in the province of Riau.This study used qualitative methods to the theory of SOR (Stimulus-Organism-reponse). The object to be studied is the brand positioning, brand identity and brand communication. Subjects were 17 people consisting of the Director, General Director, Chairman of the Company, one journalist, Kasubbid marketing Disparekraf Riau, four followers facebook account, General Manager of Grand Elite Hotel Pekanbaru, two people Followers Instagram account, two speakers Trip Riau, two journalists from other media. Data collected by interview, documentation and observation. Mechanical analysis of data using interactive data analysis model of Miles and Huberman. Mechanical examination of the validity of data using techniques extension of participation and triangulation techniques. Mechanical determination informant used purposive technique.The results show if the brand positioning element consists of identifying excellence in a way to segment the audience, presenting news in the form feauture and using high-resolution images. Then select the appropriate competitive advantage by focusing bring many visitors and promote articles through social media. And communicate and deliver the chosen position by means of presentations and exhibitions. Brand identity elements that form the brand name selection, use the tagline, and the use of corporate identity. While elements of brand communication in the form of sponsorship activities, media partners and implementation of the event. Ways considered effective to build brand awareness with levels Top Mind minds of audiences is to segment the audience, brand name selection that the content is appropriate, direct presentation of activities and implementation of the event instagram photo contest.Keywords : Branding, Brand Awareness, Tripriau.